Are factor Xa inhibitors effective thromboprophylaxis following hip fracture surgery?: A large national database study. Issue 12 (December 2017) - Campbell, Sean T.; Bala, Abiram; Jiang, Sam Y.; Gardner, Michael J.; Bishop, Julius A.
Abstract: Introduction: The purpose of this study was to evaluate the effectiveness of Factor Xa inhibitors (XaI) for thromboprophylaxis following hip fracture surgery in a large cohort of patients, and compare XaI against warfarin and enoxaparin. Methods: Patients undergoing hip fracture surgery from 2007 to 2015 were identified in a large claims database. Patients prescribed warfarin, XaI, or enoxaparin within 2 weeks of surgery were identified and grouped into cohorts. Medical comorbidities and complication incidences, including deep venous thrombosis (DVT), pulmonary embolism (PE), and bleeding complications were calculated. Chi-square analysis was performed and adjusted residuals calculated to determine significant differences. Results: DVT rates were significantly different between groups at thirty days only (5.03% warfarin, 2.91% XaI, 3.48% enoxaparin, p = 0.047). PE rates were significantly different at all time points; enoxaparin had the lowest rates. There were no differences in the rates of other complications. Discussion: XaI are an option for thromboprophylaxis in hip fracture patients, although their possible decreased effectiveness against PE compared to enoxaparin should be considered. Conclusions: This study compares the effectiveness of Factor Xa inhibitors to warfarin and enoxaparin for hip fracture patients, using a large national database. In this study, Factor Xa inhibitors had similar effectiveness for DVT prophylaxis compared to these agents.